Evaluation of Dimensionality in the Assessment of Internal Consistency Reliability: Coefficient Alpha and Omega Coefficients. Issue 4 (6th November 2015) - Green, Samuel B.; Yang, Yanyun
Abstract : In the lead article, Davenport, Davison, Liou, & Love demonstrate the relationship among homogeneity, internal consistency, and coefficient alpha, and also distinguish among them. These distinctions are important because too often coefficient alpha—a reliability coefficient—is interpreted as an index of homogeneity or internal consistency. We argue that factor analysis should be conducted before calculating internal consistency estimates of reliability. If factor analysis indicates the assumptions underlying coefficient alpha are met, then it can be reported as a reliability coefficient. However, to the extent that items are multidimensional, alternative internal consistency reliability coefficients should be computed based on the parameter estimates of the factor model. Assuming a bifactor model evidenced good fit, and the measure was designed to assess a single construct, omega hierarchical—the proportion of variance of the total scores due to the general factor—should be presented. Omega—the proportion of variance of the total scores due to all factors—also should be reported in that it represents a more traditional view of reliability, although it is computed within a factor analytic framework. By presenting both these coefficients and potentially other omega coefficients, the reliability results are less likely to be misinterpreted.